2004
DOI: 10.5713/ajas.2004.1434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Montmorillonite Nanocomposite on Mercury Residues in Growing/Finishing Pigs

Abstract: The study was conducted to evaluate the effects of montmorillonite nanocomposite (MNC) on mercury residues in growing/finishing pigs. A total of 96 cross bred pigs (Duroc×Landrace×large white, 48 barrows and gilts respectively), with similar initial weight (27.87±1.15 kg), were used in this study. The animals were randomly assigned to two concentrations of mercury (0.1 and 0.3 ppm from HgCl 2 ) and two levels (0 and 0.3%) of MNC in a 2×2 factorial arrangement of treatments. Each group has 3 pens (replications)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Multiple studies have confirmed the decontaminating properties of clay minerals. They can bind: -aflatoxins (Phillips et al, 1987(Phillips et al, , 1988Lindemann et al, 1993;Schell et al, 1993a,b;Phillips et al, 2002;Abdel-Wahhab et al, 2002;Huebner and Phillips, 2003;Rizzi et al, 2003;Shi et al, 2005Shi et al, , 2007Maciel et al, 2007;Magnoli et al, 2008;Nguyen et al, 2008), -plant metabolites (Dominy et al, 2004), -heavy metals (Hassen et al, 2003;Katsumata et al, 2003;Lin et al, 2004;Xu et al, 2004;Yu et al, 2005Yu et al, , 2008Abbes et al, 2007), -toxins (Knezevich andTadic, 1994).…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have confirmed the decontaminating properties of clay minerals. They can bind: -aflatoxins (Phillips et al, 1987(Phillips et al, , 1988Lindemann et al, 1993;Schell et al, 1993a,b;Phillips et al, 2002;Abdel-Wahhab et al, 2002;Huebner and Phillips, 2003;Rizzi et al, 2003;Shi et al, 2005Shi et al, , 2007Maciel et al, 2007;Magnoli et al, 2008;Nguyen et al, 2008), -plant metabolites (Dominy et al, 2004), -heavy metals (Hassen et al, 2003;Katsumata et al, 2003;Lin et al, 2004;Xu et al, 2004;Yu et al, 2005Yu et al, , 2008Abbes et al, 2007), -toxins (Knezevich andTadic, 1994).…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 99%
“…Xia et al (2004) reported that Cu 2+ -enriched MMT significantly decreased the frequency of diarrhoea by up to 72 per cent and significantly increased the villus height and the villus height to crypt depth ratio in the jejunal mucosa by 19 and 37 per cent, respectively. Specific physical and chemical modifications -nanocomposites (Lin et al, 2004;Xu et al, 2004;Shi et al, 2005Shi et al, , 2007Yu et al, 2008), and complexes with organic materials (Xu et al, 1997;Herrera et al, 2000Herrera et al, , 2004Koh and Dixon, 2001), are characterized by much higher adsorptive abilities than other regular clay minerals. The effect of clay minerals can also be reinforced by the addition of other components such as charcoal or antioxidants (Bonna et al, 1991).…”
Section: Modified Forms Of Clay Mineralsmentioning
confidence: 99%
“…Clays added to the diet can bind and immobilize toxic materials in the gastrointestinal tract of animals and reduce their toxicity. Several studies have confirmed the decontamination properties of clays against mycotoxins [ 11 – 17 ], heavy metals [ 18 – 24 ], and other toxins [ 25 ]. The adsorption capacity for any specific clay is determined by the fine structure of the clay particles, their surface properties and exchangeable ions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with those finding in rats [23,24]; it is shown that Cu-MMT supplemented in the Cdcontaminated diet could adsorb and remove Cd by urine or feces of the animals, then decrease Cd content in animal's body, and insure the safety of animal products. It is well known that Cu-MMT has large specific surface area, strong cation exchange capacity, and [12,25,26]; these biologically active characteristics might have adsorbed heavy metals and enhanced their excretion from the body resulting in lower heavy metals concentrations in tissues [27][28][29][30]. Consequently, it can be suggested that the ameliorative Cd toxicity potential of Cu-MMT was perhaps due to combined effects both on metal adsorption and on cation exchange, further lustrating Cd via urine and feces.…”
Section: Effects Of Cu-mmt On CD Contents In Selected Tissuesmentioning
confidence: 99%